PHYTOTHERAPY OPPORTUNITIES IN TREATMENT FOR THE RECURRENT PYELONEPHRITIS AMONG CHILDREN - O.V. Kisel'nikova; T.G. Pukhova (Педиатрическая фармакология, 2007)
Based on the literature, the sickness rate of urinary tract infections among children is increasing every year. Until now there has been much debate about the principles of the antirecurrent therapy and its efficiency among children, suffering from urinary infections, especially from pyelonephritis. This circum stance defines the search for the new efficient and safe treatment approaches and prevention methods of the urinary infection exacerbations. The researchers presented the results of the combined phytogenous medication application (canephron n, bionorica, germany) among 46 children with recurrent pyelonephritis. The combined phytogenous medication was prescribed within the decline period of the acute inflammatory process in conjunction with the antibacterial medicines. They noticed good tolerance of a medication. the full remission of pyelonephritis (over 6 months) was achieved among 28 (61%) children, while 15 (32%) patients showed some reduction of the relapse frequency (from 4–5 to 1–2 times a year). thus, the introduction of the combined phytogenous medication into the complex therapy of recurrent pyelonephritis among children allows us to reduce the frequency and duration of relapses, as well as to improve the disease prognosis, respectively.Key words: urinary infections, pyelonephritis, children, phytotherapy, combined phytogenous medication.